Pengaruh Konseling Individu Menggunakan Teknik Thought Stopping Terhadap Kepercayaan Diri Siswa di SMP Negeri 2 Bukittinggi - Ayu Lestari; Fadhilla Yusri; Junaidi; Syawaluddin (STKIP Subang, 2026)
This study aims to determine the effect of individual counseling using the thought stopping technique on the self-confidence of students at SMP Negeri 2 Bukittinggi who experience low self-confidence due to negative thoughts, fear of being ridiculed, and bullying. A pre-experimental one group pre-test post-test design was used with a population of 58 students from classes IX 3 and IX 4. A sample of 6 students was selected using purposive sampling based on certain criteria. Data analysis employed the Wilcoxon rank test. Results showed an increase in the average score from 70 in the pre-test to 97 in the post-test. The significance value of 0.028 < 0.05 indicates that the alternative hypothesis was accepted. It was concluded that individual counseling using the thought stopping technique has a significant effect on improving students’ self-confidence.